Sexual dimorphism in the incisive canal in humans: A literature review. - Fernanda Ávila-Ruiz; Francisca Ávila-Ruiz; Saskya Cuello; Alfonsina Hermosilla; Pedro Aravena (Universidad de Concepción., 2014)
Aim: To describe the morphometric characteristics of the maxillary incisor canal (IC) in human beings by gender. Material and method. Descriptive study. A systematic search for articles related to anatomical and topographical variations of the IC by sex and published in the last ten years was performed in the Medline database. Selected publications presented the following criteria: Number of samples and average values, in millimeters (mm), for length, diameter and distance from the IC to the maxillary central incisors (ICM). In addition, author and year of publication were considered. Data were presented using descriptive statistics. Results. Three studies were selected. In men, IC average dimensions were higher in diameter (2.79±0.94mm v/s 2.43±0.85mm), length (11.96±2.73mm v/s 10.39±2.47mm) and distance from the apex and middle third of the root of the MCI than in women. Conclusion. IC morphometric values were higher in men. It is important to keep in mind IC dimensions vary according to gender when planning surgeries and rehabilitations in this area of the oral cavity.